THE MEDIATING ROLE OF COMPETITIVE ADVANTAGE IN THE RELATIONSHIP BETWEEN DIGITAL COMPETENCE, DIGITAL LEADERSHIP AND VOCATIONAL TRAINING INSTITUTION PERFORMANCE - Yunita; Derriawan; Lola Fitria Sari (RADJA PUBLIKA, 2026)
This study examines the effects of digital competence and digital leadership on the performance of vocational training institutions and evaluates the mediating role of competitive advantage. Drawing on the Resource-Based View and Dynamic Capabilities perspectives, the study employed a quantitative survey design involving 180 associate trainers and managerial personnel affiliated with vocational training institutions in East Java, Indonesia. Respondents were selected through purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The results show that digital competence and digital leadership positively and significantly influence competitive advantage and institutional performance. Competitive advantage also has a strong positive effect on institutional performance and significantly mediates the effects of both digital competence and digital leadership. These findings indicate that digital resources generate superior institutional outcomes when they are strategically converted into differentiated services, efficient operational processes, and innovative business models. The study extends capability-based explanations of digital transformation in vocational education and suggests that institutional leaders should simultaneously strengthen staff digital competence, digital leadership, and the strategic use of technology to build sustainable competitive advantage and improve performance.